The Self-Esteem of Rural Children - Raymond K. Yang; Robert J. Fletsch (Journal of Research in Rural Education, 2007)
The self-esteem of children in small towns was assessed. Comparing these children's self-rated competencies to extant norms suggests that rural children's self-perceptions are not distinctly different from suburban and urban children. Rural children's feelings of self-worth and self-assessments of scholastic competence are comparable to or higher than metropolitan norms. Rural children display the same decrement in self-ratings of physical appearance as they grow older "girls more so than boys"as do urban children. Rural and urban boys rate themselves higher in athletic competence than girls. The impact of rural/urban differences on children may be less marked than suspected.